Severe COVID-19 infection in pregnancy requiring intubation without preterm delivery: A case report - Leah Hong; Nicolina Smith; Madhurima Keerthy; Monica Lee-Griffith; Robyn Garcia; Majid Shaman; Gregory Goyert (Elsevier, 2020)
Background: Coronavirus-2019 (COVID-19) is a global health crisis, but there is limited guidance for the critical care management of pregnant patients experiencing respiratory collapse. We describe our management of a peri-viable pregnant patient requiring intubation; discussion includes pharmacologic interventions, mechanical ventilation adjustments, and consideration of fetal interventions, including delivery timing. Case: A 36-year-old, gravida 2, para 1 woman positive for COVID-19 at 23 weeks of gestation with severe disease required admission to the intensive care unit and intubation. She completed 5 days of hydroxychloroquine and 7 days of prednisone. She was successfully intubated after 8 days and discharged home in a stable condition without preterm delivery on hospital day 11. Conclusion: Fortunately, the patient responded to aggressive respiratory support with intubation and mechanical ventilation early upon presentation. It is unclear whether our institution's empiric use of hydroxychloroquine and prednisone facilitated her recovery. We hope that our report helps other institutions navigate the complex care surrounding pregnant patients with severe COVID-19 pneumonia requiring intensive care.